2020
DOI: 10.1371/journal.pgen.1008803
|View full text |Cite
|
Sign up to set email alerts
|

MYO5B mutations in pheochromocytoma/paraganglioma promote cancer progression

Abstract: Identification of additional cancer-associated genes and secondary mutations driving the metastatic progression in pheochromocytoma and paraganglioma (PPGL) is important for subtyping, and may provide optimization of therapeutic regimens. We recently reported novel recurrent nonsynonymous mutations in the MYO5B gene in metastatic PPGL. Here, we explored the functional impact of these MYO5B mutations, and analyzed MYO5B expression in primary PPGL tumor cases in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 79 publications
(149 reference statements)
0
17
0
Order By: Relevance
“…A review of the English literature indicated a much lower BRAF and HRAS mutation rate in ordinary PCC/PGL and no concomitant mutations were reported ( 4 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). For ordinary GN, it is not usually associated with genetic abnormalities, and only RET gene has been considered to be causative in its pathogenesis ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…A review of the English literature indicated a much lower BRAF and HRAS mutation rate in ordinary PCC/PGL and no concomitant mutations were reported ( 4 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). For ordinary GN, it is not usually associated with genetic abnormalities, and only RET gene has been considered to be causative in its pathogenesis ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…These abnormalities reflect disruption of global vesicle trafficking, leading to a loss of the apico-basal cell polarity in epithelial cells with defective MYO5B functions. It is noteworthy that decreased MYO5B expression was observed in gastric cancer [ 129 ], whereas missense mutations of this motor protein were associated with rare neural tumors, pheochromocytoma and paraganglioma [ 130 ]. Functional studies revealed that MYO5B depletion markedly stimulates migration and Matrigel invasion of gastric cancer cells [ 129 ].…”
Section: Unconventional Myosinsmentioning
confidence: 99%
“…Functional studies revealed that MYO5B depletion markedly stimulates migration and Matrigel invasion of gastric cancer cells [ 129 ]. Furthermore, overexpression of MYO5B mutants, characteristic of neural tumors, accelerates cancer cell migration along with stimulation of cell proliferation [ 130 ]. The reportedly contrasting functional roles of MYO5A and MYO5B in cancer are puzzling, given the high sequence and structural similarity of these motors.…”
Section: Unconventional Myosinsmentioning
confidence: 99%
“…TERT promoter mutations or hypermethylation and structural TERT rearrangement or amplification of TERT locus) confer information on metastatic progression and poor prognosis of patients with Krebs cycle-associated paraganglionic tumours [48]. Moreover, somatic MYO5B mutations leading to deregulated Rab and Rac/Rho GTPase pathways which appear to be preferentially enriched in PPGL-affected patients with metastatic disease and germline SDHB mutations [47,49].…”
Section: Molecular Mechanisms In Ppgl Tumourigenesismentioning
confidence: 99%